DNA Probes Using Fluorescence Resonance Energy Transfer (FRET): Designs and Applications - Didenko, Vladimir V. (2001)
Fluorescence resonance energy transfer (FRET) is widely used in biomedical research as a reporter method. Oligonucleotides with a DNA backbone and one or several chromophore tags have found multiple applications as FRET probes. They are especially advantageous for the real-time monitoring of biochemical reactions and in vivo studies. This paper reviews the design and applications of various DNA-based probes that use FRET. The approaches used in the design of new DNA FRET probes are discussed.